Public views on drought mitigation: evidence from the comments sections of on-line news sources - Russell-Verma, Sharon; Smith, Heather M.; Jeffrey, Paul (Taylor and Francis, 2015)
During the spring of 2012 much of the south-east of England was under water use restrictions, as a result of two consecutive dry winters. The drought highlighted the region's vulnerability to this natural hazard and emphasized the issues associated with water shortages and the need for drought mitigation measures. Using qualitative content analysis of online news articles (n = 14) and their associated comments from readers (n = 1298) we explore both public preferences for drought mitigation options and the underpinning reasoning used to justify such preferences. Findings suggest that supply side interventions attract more intense commentary and divide opinion to a greater extent than demand side strategies and that dialogue around mitigation options is characterised by a pronounced concern for the relative social justice of choices. The study also generates important lessons about the structured use of on-line public opinion sources and we offer conclusions about how these might best be utilised in the future.
Keywords: drought; mitigation; on-line; preferences; news